MENDAMPINGI KEGIATAN BOLA GEMBIRA OLEH LPP TVRI KALIMANTAN TENGAH DI CAR FREE DAY (CFD) PALANGKARAYA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DAN PEMBERDAYAAN UMKM - Masti Masti; Vivy Kristinae; Raditya Fernando; Selvia Selvia (Yayasan Nusa Cendekia Global, 2026)
The Bola Gembira activity by LPP TVRI Central Kalimantan is a community service program that aims to increase public participation in accessing the FIFA World Cup broadcast for free, fair, and inclusive. This activity is carried out through educational-participatory methods, namely, mentoring, socialization, and empowerment for MSMEs, which includes the distribution of brochures, education on how to access TVRI broadcasts, registration information for the FIFA World Cup watching program, and direct interaction with the community. In addition, activities are packaged in the form of entertainment and social interaction such as gymnastics, fun walks, and exciting activities to increase community involvement. The results of the activities showed that there was an increase in public understanding of public access to public broadcasts and wider participation in the activities held. This program also has an economic impact on MSMEs, where business actors can participate in watching activities together, namely providing their business location as a venue for holding events, so that it has the potential to increase sales and expand their business market. Thus, this program not only increases access to information and entertainment, but also strengthens TVRI's role in supporting local economic empowerment.